2015
DOI: 10.17135/jdhs.2015.15.5.551
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Emotional Leadership, Commitment, Patient Orientation, and Job Performance in Dental Hygienists

Abstract: This study intended to search for measures to effectively improve and manage the job performance and personality of dental hygienists. In this study, the effects on job performance of the following variables were analyzed: emotional leadership, commitment, and patient-orientation. The subjects of the study were 328 dental hygienists who were working in a dental clinic and the assessment was made based on a self-administered questionnaire. T-test, one-way ANOVA, and Stepwise multiple regression were performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Kim and Kim 25) found that the older the age, the higher the job performance ability, the higher the age, the higher the job performance, the higher the job performance, the higher the bachelor's degree or higher, the more total or current work experience, and the higher the position. Kim and Han 6) showed similar results as in this study, showing that they were 36 years old or older, 11 years of work experience or more, and the reception and counseling areas or management and administration areas were high, and the position was higher in the case of the head of the department. The higher the age, experience, or position, the higher the role will be as a manager at the dental clinic.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Kim and Kim 25) found that the older the age, the higher the job performance ability, the higher the age, the higher the job performance, the higher the job performance, the higher the bachelor's degree or higher, the more total or current work experience, and the higher the position. Kim and Han 6) showed similar results as in this study, showing that they were 36 years old or older, 11 years of work experience or more, and the reception and counseling areas or management and administration areas were high, and the position was higher in the case of the head of the department. The higher the age, experience, or position, the higher the role will be as a manager at the dental clinic.…”
Section: Discussionsupporting
confidence: 82%
“…Various causes were suggested for job performance, and Park and Lee 5) stated that interpersonal relationship competency, self-regulation competency, and basic dental hygiene management competency affect the job performance of dental hygienists. Kim and Han 6) stated that patient orientation, relationship management ability, age, social awareness ability, and hospital type affect job performance.…”
Section: Introductionmentioning
confidence: 99%